Mental health screening in Cystic Fibrosis as an intervention: Patient and caregiver feedback on improving these processes. (October 2022) - Landau, Edwina C.; Verkleij, Marieke; Graziano, Sonia; Quittner, Alexandra L.; Georgiopoulos, Anna M.; Smith, Beth A.; Schechter, Michael S.; Abbott, Janice; ,
Highlights: Integration of mental health screening has become a standard of CF care. CF Patient and caregiver assessment on processes and benefits of MH screening. Comparisons between Europe and US. MH seen as an intervention itself and provides motivation to pursue MH support. CF patients and caregivers view MH screening as an important part of CF care.